Pengembangan modul geografi berbasis pendekatan saintifik pada materi dinamika hidrosfer - Muhammad Sultoni; Budijanto Budijanto; Sugeng Utaya (Universitas Negeri Malang, 2023)
Learning in the 2013 curriculum scientific learning process through 5 activities: observing, asking, gathering information, associating, and communicating. Modules are one of the teaching materials that can help scientific learning. This study aims to develop a geography module based on a scientific approach to the hydrosphere dynamics material. The development procedure adopts the ADDIE model with five stages of analysis, design, and development, implementation, and evaluation. However, the research and development of this module has only reached the development stage due to limited time, effort and cost. The subjects of this study were experts (material, media, and language) to determine the level of module validity and prospective users (teachers and students) to determine the response to the module. Data collection using a validation questionnaire to obtain quantitative data and qualitative data. The results of the research and development of the module are very valid/feasible to use with a score from the material validator of 91.4 percent, 100 percent media, and 100 percent language. Prospective users (teachers and students) respond to the module, which shows the module